Rhombic dodecahedral Ag3PO4 architectures: controllable synthesis, formation mechanism and photocatalytic activity. Issue 9 (9th February 2016) - Dong, Chao; Wang, Jing; Wu, Kong-Lin; Ling, Min; Xia, Shan-Hui; Hu, Yu; Li, Xiao; Ye, Yin; Wei, Xian-Wen
Abstract : A facile surfactant-assisted ion-exchange method has been developed to prepare rhombic dodecahedral Ag3 PO4 sub-microcrystals through employing uniform Ag2 CO3 sub-microrods as a precursor for the first time. Abstract : A facile surfactant-assisted ion-exchange method has been developed to prepare rhombic dodecahedral Ag3 PO4 sub-microcrystals which are ca. 250–600 nm in size through employing uniform Ag2 CO3 sub-microrods which are ca. 250–450 nm in diameter and 1–2 μm in length as a precursor for the first time. A series of contrast experiments indicates that the dosages and types of surfactants and different anion sources have a great influence on the formation of the Ag3 PO4 rhombic dodecahedra. Based on time-dependent experiments, a reasonable so-called precipitation–dissolution–recrystallization growth mechanism for the Ag3 PO4 rhombic dodecahedra has been proposed. The as-prepared sample exhibits higher photocatalytic activity than both commercial TiO2 (P25) and irregular Ag3 PO4 particles toward degradation of rhodamine B (RhB) aqueous solution under visible light irradiation. The pseudo-first-order rate constant for RhB photodegradation by the rhombic dodecahedral Ag3 PO4 (0.164 min −1 ) is about 7 and 2.5 times that of P25 and irregular Ag3 PO4, respectively.